PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) TIPE PERCONTOHAN TERHADAP PRESTASI BELAJAR DAN TANGGUNG JAWAB MATERI GLOBALISASI - Permatasari, Desty Ratna (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research aims to find out the effectiveness of Value Clarification Technique (VCT) learning model of exampling type toward learning achievement for the fourth graders of SD N 1 Tinggarjaya in Civic Education The subject on the topic of Globalization. This is an experimental design with Randomized control group pretest-posttest research design. The subject of the research was the student off for the Fourth Graders of SD N 1 Tinggarjaya academic year 2014/2015 consisting of 32 students of class IVA as control, class and 33 students of class IVB as an experimental class. The technique of the data collection was by posttest in the form of filling short answer and statement with 10 items., while for the student’s responsibility technique, it used the questionnaire technique. The data had been gained were then analyzed to test a hypothesis by using the formula of the t-test. Based on the result of the research, it was found that the application of VCT learning model exampling type affected on learning achievement for the fourth graders of SD N 1 Tinggarjaya in Civics Education Subject on the topic of Globalization.